2009
DOI: 10.1118/1.3271338
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and empirical investigations of for nearly water‐equivalent radiotherapy dosimetry

Abstract: In conclusion, the authors demonstrate that KCl : Eu(2+)-based dosimeters can be accurately modeled by a MC method and that 2D KCl : Eu2+ films of the order of 1 microm thick would have minimal energy dependence. The data support the future research and development of a KCl : Eu2+ storage phosphor-based system for quantitative, high-resolution multidimensional radiation therapy dosimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Storage phosphors, or computed radiography (CR) plates, could also potentially provide a 2D dose distribution, but they have been generally used in high energy radiation therapy situations, unlike the diagnostic energy range detailed in this study. 19,20 In addition, although storage phosphor plates come in a variety of sizes, they cannot be submerged in any type of liquid since the liquid would render the plate unreadable in the CR plate readout device.…”
Section: Introductionmentioning
confidence: 99%
“…Storage phosphors, or computed radiography (CR) plates, could also potentially provide a 2D dose distribution, but they have been generally used in high energy radiation therapy situations, unlike the diagnostic energy range detailed in this study. 19,20 In addition, although storage phosphor plates come in a variety of sizes, they cannot be submerged in any type of liquid since the liquid would render the plate unreadable in the CR plate readout device.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, increased energy dependence occurs. Zheng et al (Zheng et al, 2010) confirmed this suggestion through Monte Carlo simulations. This reasoning also explains why AgBr radiographic film, with a sensitive layer on the order of a few microns thick, did not show a strong energy-dependence as would be expected due to its high effective Z of 43 (Low et al , 2011).…”
Section: Discussionmentioning
confidence: 71%
“…Recently, we have shown that KCl:Eu 2+ -based dosimeters provide similar energy response as radiographic film [2, 3]. The Z eff is 18, which is much closer to tissue than BaFBrI or CsBr.…”
Section: Introductionmentioning
confidence: 99%